Boosting Quality Performance Through Customer Knowledge Management and Service Innovation Capability in the Automotive Industry - Jaludin, Janteng; Cheng, Ling Tan; Fernando, Yudi (Academic Conferences and Publishing International Limited Reading, UK, 2018)
The intention of service innovation capability in the automotive industry is seen as a sustainable competitive advantage that drives the firm’s quality performance. It is a holding ability to absorb, adapt and transform a given technology into the operational, managerial and assignable routines that may lead to revenue. The interaction of various elements like strategy, resources, and processes as innovation capability enables the success of the entire quality performance in the automotive industry. The improvement of quality performance is a vital source of competition among the automotive service centres. The quality performance in automotive service centres usually refers to the service quality in marketing term. To differentiate companies’ strategy, managers have to look into the new idea from external sources especially customers. External sources such as customer knowledge are significant and noteworthy because the customer is now more active and innovative in the service encounter. The communication among the customers and organisations around the world can be very efficient through the power of technology. Although this issue is essential, however, the number of studies related to the importance of customer knowledge management among managers in the automotive service centres are still lacking in the country. To solve this problem, the primary goal of this study is to investigate the relationship of customer knowledge management and service innovation capability; and to identify the factors that can affect the level of quality performance of the automotive service centres in Malaysia. The previous studies have confirmed that customer knowledge management has a significant effect on service innovation capability, while service innovation capability also has a positive relationship with the increasing level of quality performance. It proposed that service innovation research be regularly conducted in the organisation and organising events with customers to be actively involved in product and service design. This initiative should be given to new managers and poorly performing service centres. This paper is expected to assist academician, practitioners and local car manufacturer service centres in understanding knowledge sharing concept and enhancing quality performance among automotive service centres in Malaysia.